2021
DOI: 10.1177/11206721211020646
|View full text |Cite
|
Sign up to set email alerts
|

The significance of primary monocanalicular silicone tube intubation in late surgical treatment in children

Abstract: Purpose: To evaluate the effect of monocanalicular silicone tube intubation outcomes as an initial surgical treatment in children older than 1 year old with primary nasolacrimal obstruction. Methods: Probing or monocanalicular silicone tube intubation was performed as primary surgical treatment on 12–48 months old children with primary nasolacrimal obstruction. Probing was performed on 53 eyes of 43 patients and silicone tube intubation on 45 eyes of 39 patients. Treatment was considered successful after impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Considering the selfselection process and the accumulation of more cases of complex obstructions in older children, probing is insufficient to overcome the stenosis in the lacrimal pathways. Interestingly, some authors have noticed an age-related decline in the success of probing in CNLDO, without such a trend in those who underwent NLD intubation in their series [34,35].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Considering the selfselection process and the accumulation of more cases of complex obstructions in older children, probing is insufficient to overcome the stenosis in the lacrimal pathways. Interestingly, some authors have noticed an age-related decline in the success of probing in CNLDO, without such a trend in those who underwent NLD intubation in their series [34,35].…”
Section: Discussionmentioning
confidence: 91%
“…There is some controversy in literature regarding the prognosis in older children with CNLDO. While some authors have reported decreased success in older children [18,[24][25][26][27][28][29][30][31][32], others have found similar outcomes in children of different ages [15,[33][34][35] and some have emphasized on the role of the type of obstruction (complex vs. simple), rather than the age per se [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%